2023
DOI: 10.1177/03611981231155169
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impacts on Online and In-Store Shopping Behaviors: Why they Happened and Whether they Will Last Post Pandemic

Abstract: Throughout the COVID-19 pandemic, people’s online and in-store shopping behaviors changed significantly. As the pandemic subsides, key questions are why those changes happened, whether they are expected to stay, and, if so, to what extent. We answered those questions by analyzing a quasi-longitudinal survey dataset of the Puget Sound residents (Washington, U.S.). We deployed structural equation modeling (SEM) to build separate models for food, grocery, and other items shopping to explore the factors affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Prior research has found that consumers who rely heavily on product touch do prefer to make their purchase decisions through traditional offline stores, as a physical prepurchase touch is feasible (Citrin et al, 2003). Consumers' It is suggested that the brain may experience the mental simulation of touch without any actual tactile input (Ebisch et al, 2008). Overmars and Poels (2015) demonstrate that in online shopping, simulated TSs can be a crucial factor for understanding products.…”
Section: Organism: Tactile Sensations Cognitive Effort and Affective ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has found that consumers who rely heavily on product touch do prefer to make their purchase decisions through traditional offline stores, as a physical prepurchase touch is feasible (Citrin et al, 2003). Consumers' It is suggested that the brain may experience the mental simulation of touch without any actual tactile input (Ebisch et al, 2008). Overmars and Poels (2015) demonstrate that in online shopping, simulated TSs can be a crucial factor for understanding products.…”
Section: Organism: Tactile Sensations Cognitive Effort and Affective ...mentioning
confidence: 99%
“…Bringing shops into homes and consumers embracing more digital technologies are among the outcomes of the pandemic (Sheth, 2020; Truong & Truong, 2022). More than 75% of new online shoppers, who started to shop online since the pandemic, believe that they will continue to purchase online afterward (Diaz‐Gutierrez et al, 2023). Additionally, there has been continuous development in technology in the retailing environment.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the outbreak has been declining, consumers' positive attitude and preference for online shopping continue to persist and are expected to increase even further in the future. In comparison, in-store shopping has decreased proportionally to one-third to half of online shopping instances [3]. Nevertheless, it does not necessarily mean that all products available on online shopping platforms will be popular and produce massive sales.…”
Section: Introductionmentioning
confidence: 99%
“…before the pandemic, rose to 89% at wave 1, and subsequently decreased to 72.5% at wave 3 of the pandemic (Baumann et al, 2023). Online shopping, however, experienced a sustained increase suggested by researchers during the lockdown period as well as the post-pandemic era (Brůhová Foltýnová and Brůha, 2024;Diaz-Gutierrez et al, 2023).…”
mentioning
confidence: 97%
“…before the pandemic, rose to 89% at wave 1, and subsequently decreased to 72.5% at wave 3 of the pandemic (Baumann et al, 2023). Online shopping, however, experienced a sustained increase suggested by researchers during the lockdown period as well as the post-pandemic era (Brůhová Foltýnová and Brůha, 2024;Diaz-Gutierrez et al, 2023).Observing huge shifts to WFH and online shopping, these ICT-based activities as part of travel demand management, provide transportation planners and policymakers with an opportunity to address transportation system issues such as urban congestion and GHG emissions (Hensher et al, 2022;Shabanpour et al, 2018). Hence, it is critical to understand what in uences individuals' decisions on WFH and online shopping, as well as the interrelationship between these two behaviors.…”
mentioning
confidence: 98%